Demographic, Behavioural, and Biological Factors Seen in Men Who Have Sex with Men with Salmonella spp.: A Systematic Review - Vidhushan Sivachandran; Natasha Wahab; Vaibhav Dubey; Daniel Richardson; Carrie Llewellyn (Venereology)
Background: The sexual transmissibility of enteric pathogens, including Salmonella spp., has been described in men who have sex with men (MSM). However, the factors seen in MSM with Salmonella spp. are poorly understood. Method: We aimed to systematically review the literature to explore any factors seen in MSM with Salmonella spp. (MSM). We searched six databases—Medline, PubMed, CINAHL, Embase, Emcare, and Global Health—in April 2024 for manuscripts which contained primary peer-reviewed data in English and the measurement of any risk factors observed in MSM with Salmonella spp. This review was registered on PROSPERO (CRD42023472864). Results: Eleven manuscripts were included in the final review and highlighted demographic (living with HIV), behavioural (oral–anal sex, receptive and penetrative anal sex, hand licking to stimulate their partner, group sex, non-condom use), and biological (co-infection with CMV, Mycobacterium avium complex, Strongyloides stercoralis, Blastocystis hominis, Klebsiella spp. Herpes simplex virus, Cytomegalovirus, Cryptosporidium, Histoplasmosis, Shigella spp.; previous infection with Treponema pallidum, Neisseria gonorhoeae, Chlamydia trachomatis and hepatitis B; and antimicrobial treatment failure) factors seen in MSM with Salmonella spp. Conclusion: Despite a limited number of manuscripts and individuals, this review highlighted some potential demographic, behavioural, and biological factors implicated in the transmission of Salmonella spp. in MSM. These data will provide insights for future guidelines, public health control strategies, and research.